(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
Laser additive manufacturing (LAM) enables the fabrication of customized components. In medical applications where components contain both dense and lattice material, the process has a significant influence on the design process impacting mechanical properties and manufacturing accuracy. Currently, both build rate and strut thickness of thin-walled lattices cannot be scaled leading to low build rates, inaccurately fabricated lattices, and high unit costs. Here, a method is presented to determine the melt pool geometry material independently. The proposed scaling laws can be utilized for scaling the build rate, precise fabrication of thin-walled lattice structures, and correlating process parameters with resulting component properties.